Video capsule endoscopy: Initial experience from a tertiary care center in Sri Lanka - Perera, Dinesh Rangika; Rangana, Piyal; Aryasingha, Sanjeewa (Asian Journal of Medical Sciences, 2021)
Background: Since its global introduction in 2000, capsule endoscopy (CE) has revolutionized the evaluation of small bowel disease. Aims and Objective: The aim of this study was to share our experience with CE including the findings and its diagnostic yield. Materials and Methods: A retrospective study was carried out at Colombo South Teaching Hospital of Sri Lanka. Data of patients who underwent CE from its initiation in 2017 until June 2020 were obtained from the hospital computer database. These included the patient demographics, indications for the study, quality of bowel preparation, and its findings. Results: The study included 54 patients with a mean age of 55 years. Mean gastric time and small bowel transit time were 52 and 272 min, respectively. Forty-five CE studies were done for the evaluation of small bowel bleeding and an abnormal study was found in 26 (57.78%) patients. Small intestinal ulcers and erosions were the most frequently found abnormality (n=16, 35.56%) followed by tumors (n=5, 11.11%). Active bleeding was evident in 14 (31.11%) patients. Overall diagnostic yield was higher in those with a history of overt bleeding (n=15, 71.43%) compared to occult bleeding (n=11, 45.83%). Most patients who were evaluated for abdominal pain and diarrhea had normal CE except for two who had small intestinal ulcers and subepithelial lesions. Only one case was complicated with capsule retention. Conclusion: CE is a useful investigation for the evaluation of small bowel disease, particularly in suspected small bowel bleeding. In contrast to western population, ulcers and erosions were the more frequently found abnormalities seen in local setting.